CD 69 antigen of human lymphocytes is a calcium-dependent carbohydrate-binding protein - Bezouska, K; Nepovím, A; Horváth, O; Pospísil, M; Hamann, J; Feizi, T (Biochemical and biophysical research communications, 1995)
CD69 is a signal transducing molecule of hematopoietic cells. Previous molecular cloning of CD69 has revealed a type II transmembrane orientation and the presence of an extracellular domain related to the Ca(2+)-dependent (C-type) animal lectins. As the predicted amino acid sequence for the lectin-like domain is highly divergent from those of other C-type lectin-like proteins - a feature shared with NKR-P1 of natural killer cells - CD69 and NKR-P1 are among proteins assigned to a separate group, group V. To initiate ligand identification studies, we have prepared soluble forms of CD69 protein by bacterial expression of its extracellular portion. We show that cysteine 68 located in the short membrane-proximal neck region of CD69 which adjoins the C-terminal lectin-like domain is a critical element for dimerization. We have evidence that the soluble dimeric CD69 has a tight association with calcium, a feature shared with NKR-P1, and that it is a carbohydrate-binding protein with N-acetyl-D-glucosamine and N-acetyl-D-galactosamine as the best inhibitors: 4-8 x 10(-5) M giving 50% inhibition of binding to N-acetyl-D-glucosamine neoglycoprotein. Thus, the tight association with calcium and high affinities for carbohydrate binding appear to be features of at least two members of the C-type lectin group V.
Keywords: kinetika; Molecular Sequence Data; Chromatography, Gel; elektroforéza v polyakrylamidovém gelu; sérový albumin hovězí; Molecular Weight; sekvence aminokyselin; monosacharidy; Killer Cells, Natural; Antigens, Differentiation, T-Lymphocyte; Lymphocytes; molekulová hmotnost; Serum Albumin, Bovine; rekombinantní proteiny; vápník; Lectins, C-Type; Acetylglucosamine; lymfocyty; lektiny typu C; Cloning, Molecular; gelová chromatografie; diferenciační antigeny T-lymfocytů; Calcium; Electrophoresis, Polyacrylamide Gel; Escherichia coli; lektiny; Lectins; Humans; Amino Acid Sequence; Antigens, CD; Kinetics; klonování DNA; Monosaccharides; molekulární sekvence - údaje; buňky NK; CD antigeny; lidé; Recombinant Proteins; acetylglukosamin